(untitled) (Confluenţe Bibliologice, 2013)
In our brief study compares the poem of the famous Moldovan poet Dumitru Matcovschi and mundane miniature classic literature in Yiddish Ikhil Shraibman. It should be noted that we do not set ourselves the task of identifying their political positions and ideologies. In our text from the same village of the tragic history of Vadul-Rashkova appear as countrymen and creators of their own artistic worlds. Creativity, unique sense of humor and masterly skill of the artists words please the eye of grateful readers and awaken in their hearts the desire to live a full life, read, laugh, empathize and thank God for the talent he has given to our countrymen and contemporaries.